Підвищення інноваційної активності на промислових підприємствах України шляхом трансферу технологій - Balashova, Olena V. (Institute of Industrial Economics of NAS of Ukraine, 2023)
The article examines measures of step-by-step promotion of innovations at industrial enterprises of Ukraine. Economic factors hindering the implementation of new technologies at enterprises are highlighted. This is caused primarily by the fact that during the global economic crisis, enterprises and industries that actively implement and use innovative technologies are competitive. At the same time, Ukraine continues to develop as a country with a high share of raw materials industries, and innovative development has not become one of the main signs of the growth of the national economy. Although positive trends were observed for several years, they were mainly temporary in nature and were replaced by opposite shifts in the economy, which characterizes innovation processes in Ukraine as unstable and devoid of clear long-term incentives for innovative activity. In these conditions, there is a need to identify key problems that hinder the development of innovative activities of domestic enterprises, and to find ways to solve them.The implementation of a marketing strategy for the promotion of innovative projects at small and medium-sized industrial enterprises and the transfer process of innovations at large enterprises to gain their competitive advantages in domestic and foreign markets is substantiated. Emphasis is placed on the existing features of implementation in the conditions of digitalization of global business, which is confirmed by the construction of appropriate layouts and schemes.An overview was carried out to what extent all these technological innovations lead to deep and large-scale changes in the systemic character of economic (and not only economic) relations, reformatting of their very foundations and the emergence of new socio-economic institutions. Thus, the basis of modern relations is not only and not so much property relations, but the possibility of access to certain goods, resources, and information. Radical technological innovations to one degree or another affect and will increasingly affect the technologies of commercial operations, the role and forms of activity of their commercial intermediaries.The process of technology transfer to the real sector of the economy has been improved, which takes into account the joint refinement of innovative projects of innovators with enterprises that are potential bases of implementation, with the implementation of the activities of the Coordination Center.